2012
DOI: 10.1029/2011gl050659
|View full text |Cite
|
Sign up to set email alerts
|

Where is the ideal location for a US East Coast offshore grid?

Abstract: 1] This paper identifies the location of an "ideal" offshore wind energy (OWE) grid on the U.S. East Coast that would (1) provide the highest overall and peak-time summer capacity factor, (2) use bottom-mounted turbine foundations (depth ≤50 m), (3) connect regional transmissions grids from New England to the Mid-Atlantic, and (4) have a smoothed power output, reduced hourly ramp rates and hours of zero power. Hourly, high-resolution mesoscale weather model data from 2006-2010 were used to approximate wind far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 14 publications
1
31
0
Order By: Relevance
“…) occur off the eastern and western coasts of North America, as previous research (Dvorak et al 2010;Sheridan et al 2012) has suggested. This result is due, for the west coast, to the land-sea pressure gradient that creates a persistent marine boundary layer (e.g., Dorman and Winant 1995;Dvorak et al 2010;Jiang et al 2008).…”
mentioning
confidence: 51%
See 4 more Smart Citations
“…) occur off the eastern and western coasts of North America, as previous research (Dvorak et al 2010;Sheridan et al 2012) has suggested. This result is due, for the west coast, to the land-sea pressure gradient that creates a persistent marine boundary layer (e.g., Dorman and Winant 1995;Dvorak et al 2010;Jiang et al 2008).…”
mentioning
confidence: 51%
“…2b). Two significant synoptic features at work in this region to affect surface wind speeds would be the strength and presence of the warm-season-dominant Bermuda-Azores subtropical high and positioning of the storm track for the cool season (Dvorak et al 2012). As a result, cool-season WBs for region I are likely due to frequent low pressure systems associated with an active and persistent storm track that appears to have varied little since 1979.…”
Section: A Frequencies Of Wind Lulls and Wind Blowsmentioning
confidence: 99%
See 3 more Smart Citations